The Covid-19’s Negative Impacts on Nepalese Economy with a South Asian Perspective: Strategic Response on Post Pandemic Control - Chaudhary, Manoj Kumar (Jurnal Ilmiah Peuradeun, 2021)
The paper investigated and explored experts’ opinions regarding the post-pandemic control strategies within the South Asian perspective to make the Nepalese economy robust. The study was based on qualitative methods of analysis and the method of the study had been classified into two parts: Primary & Secondary. For secondary, data were collected through published reports, journal articles, the daily national newspaper, media, and Television coverage & personal observation, and experience. Whereas, for primary data, the study was carried out considering the way to control the post-pandemic effects on developing economies particularly in Nepal. The result of the study depicted that the post control of covid-19 effects on economic revival policies should prioritize sectorial concerns on the agriculture and industry sector of the economy over service sector and remittance. Therefore, for the pandemic recovery issue, the government and private sector’s role is to jointly solicit a model Public, Private, Partnership for the firm relief of economic stability. Thus, the paper concluded that there is an urgent need to prepare the post control strategy to minimize economic vulnerability. In this situation, Nepal needs strategies for good governance rather than a complex and mysterious plan.